2023
DOI: 10.1177/11782218231158031
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use Disorder and Associated Factors Among Elderly in Ethiopia

Abstract: Background: The aim of this study was to investigate the magnitude and associated factors of alcohol use disorder among the elderly living in 3 towns in South West Ethiopia. Method: Cross-sectional community-based study was done among 382 elderly people aged 60 or more from February to March 2022 in South West Ethiopia. The participants were selected by a systematic random sampling method. Alcohol use disorder, quality of sleep, cognitive impairment, and depression were assessed by using AUDIT, Pittsburgh Slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Only one HIC study found associations between medical problems like higher body mass index and being non-diabetic than diabetic 39 and problem drinking. In contrast, eight studies from LMICs found associations between medical problems like chronic disease, 63 92 high blood pressure, 91 122 obesity, 93 self-reported physical comorbidities, 112 traffic injury 130 and problem drinking. Only a few studies from LMICs found associations between problem drinking and less psychosocial support, 59 117 118 more impaired functioning, disability, poorer quality of life, cognitive impairment and poor sleep quality.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Only one HIC study found associations between medical problems like higher body mass index and being non-diabetic than diabetic 39 and problem drinking. In contrast, eight studies from LMICs found associations between medical problems like chronic disease, 63 92 high blood pressure, 91 122 obesity, 93 self-reported physical comorbidities, 112 traffic injury 130 and problem drinking. Only a few studies from LMICs found associations between problem drinking and less psychosocial support, 59 117 118 more impaired functioning, disability, poorer quality of life, cognitive impairment and poor sleep quality.…”
Section: Resultsmentioning
confidence: 88%
“…Hazardous/harmful alcohol use, also known as harmful/hazardous drinking, probable AUD, risky alcohol use, high-risk drinking, or hazardous, harmful, or dependent alcohol use, was defined as a score of ≥8 on the AUDIT in most studies including studies conducted in New Zealand, 53 Norway, 55 Brazil, 107 108 South Africa, 61 101 India, 109–112 Kenya, 113 Uganda, 114 Nepal, 115 Ethiopia, 63 116–118 Malaysia, 89 Thailand 90 119 and Suriname. 60 This definition is in keeping with the World Health Organization (WHO) recommended cut-offs for problem drinking on the AUDIT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation